Synthesis and Characterization of Mixed Ligand Complexes of Praseodymium(III), Neodymium(III), Samarium(III), Gadolinium(III) and Dysprosium(III) with Piperidinobenzylurea
A series of mixed ligand complexes of the lanthanide metal ions, viz., Pr(III), Sm(III), Nd(III), Gd(III) and Dy(III) with a Mannich base derived form urea, piperidine and benzaldehyde and various anions such as chloride, nitrate, acetate, thiocyanate and perchlorate have been synthesized and characterized. The analytical data include elemental analysis, determination of molar mass, conductivity, magnetic, spectral and thermal studies. The complexes exhibit the following general formulae: (i) [Ln(PBU)2X3] and (ii) [Ln(PBU